2020
DOI: 10.3389/fmars.2020.547896
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Water Soft Corals (Cnidaria: Nephtheidae) as Habitat for Juvenile Basket Stars (Echinodermata: Gorgonocephalidae)

Abstract: Nephtheidae soft corals are a common component of benthic ecosystems in the Northwest (NW) Atlantic and in the Arctic, but little is known about their functional roles. Here we investigated their role as habitat for basket stars (Ophiuroidea). By examining over 4500 soft coral colonies of Drifa glomerata, Duva florida, Gersemia spp., and Pseudodrifa racemosa collected during trawl surveys in the regions of Newfoundland, Labrador and West Baffin Bay, we show that Nephtheidae soft corals are habitat for juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…Soft corals reported in this study are known to provide habitat to juvenile basket stars (Gorgonocephalus sp. ; Neves et al 2020). In fact, juvenile basket stars were observed attached to soft coral colonies at several instances in the Nain archipelago, and the single observation of an errant basket star in this study was also reported there.…”
Section: Vme Indicatorssupporting
confidence: 77%
See 2 more Smart Citations
“…Soft corals reported in this study are known to provide habitat to juvenile basket stars (Gorgonocephalus sp. ; Neves et al 2020). In fact, juvenile basket stars were observed attached to soft coral colonies at several instances in the Nain archipelago, and the single observation of an errant basket star in this study was also reported there.…”
Section: Vme Indicatorssupporting
confidence: 77%
“…However, our in situ observations in Nain reinforce that co-occurrence rates might change spatially and that at this site Gersemia sp. might provide habitat to juvenile basket stars at potentially higher occurrence rates than those described by Neves et al (2020) based on physical specimens. Nephtheidae soft coral gardens have also been suggested for consideration as VME indicators (Long et al 2020).…”
Section: Vme Indicatorsmentioning
confidence: 86%
See 1 more Smart Citation
“…These gardens are important for the wider faunal community. They provide a significant structural role, as octocorals house unique commensal species on their branches [9], harbour eggs of charismatic species such as catsharks [10] and cephalopods [11], and act as a nursery for juvenile invertebrates, e.g., basket stars [12]. Many corals are slow-growing and long-lived, with radiocarbon ( 14 C) ageing of some individuals of Paramuricea sp.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, vulnerable taxa can support elevated biodiversity (Cerrano et al 2010). For example, deepwater corals and sponges are habitat-forming species, modifying environmental conditions with their presence (Zedel and Fowler 2009) and creating foraging (Buhl- Mortensen 2004, Gale et al 2013), nursery (Aldrich and Lu 1968, Baillon et al 2012, Neves et al 2020, and refuge (Wulff 2006) areas for other taxa. At the same time, their sessile nature, fragile structures, and slow growth make them extremely vulnerable to disturbance from human activities, such as bottom-contact trawling, from which they can take decades or more to recover (Neves et al 2014).…”
Section: Introductionmentioning
confidence: 99%